Clinical and experimental rationale for using phenylephrine with hypromellose for the treatment of extra accommodation strain in patients with myopia - M.V. Makhova; E.V. Shikh; V.V. Strakhov; D.S. Blinov; G.K. Poluosmak; E.V. Semeleva; E.V. Blinova (РМЖ "Клиническая офтальмология")
M.V. Makhova1, E.V. Shikh2, V.V. Strakhov1, D.S. Blinov3,4, G.K. Poluosmak2, E.V. Semeleva5, E.V. Blinova2,4 1Yaroslavl State Medical University, Yaroslavl, Russian Federation 2I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation 3Dmitry Rogachev National Medical Research Center of Pediatric Hematology, Oncology and Immunology, Moscow, Russian Federation 4National Research Nuclear University MEPhI, Moscow, Russian Federation 5N.P. Ogarev National Research Mordovia State University, Saransk, Russian Federation Aim: to perform a comparative analysis of the clinical efficacy of 2.5% phenylephrine with and without hypromellose for the treatment of extra accommodation strain in schoolchildren with myopia and to perform an experimental evaluation of the pharmacological effective of active ingredient of the finished dosage form (FDF) of preparations containing 2.5% phenylephrine with and without excipients. Patients and Methods: this clinical study enrolled 122 schoolchildren, 11–17 years old, with extra accommodation strain of various severity. The children were split into two groups. The group 1 patients received Irifrin® BK, containing 2.5% phenylephrine with hypromellose, one eye drop at the bedtime during 30 days, and the group 2 patients — Preparation A (2.5% phenylephrine without hypromellose) according to the same dosage regimen. The accommodative function was evaluated using the Speedy-i accommodation analyzer, and the coefficients of accommodation response before and 30 days after the treatment were determined. The experimental study was carried out in 40 sexually mature male rabbits of the Soviet Chinchilla breed to evaluate the development and duration of mydriatic effect and to measure the concentration of active ingredient — phenylephrine with hypromellose, as an excipient (Irifrin® and Irifrin® BK), phenylephrine without hypromellose (Preparation A) and phenylephrine with sodium hyaluronate as an excipient (Preparation B) in the aqueous humor within the eye anterior chamber using high-performance gas-liquid chromatography with tandem mass spectrometric detection. Results: the drug therapy of extra accommodation strain comprising 2.5% phenylephrine hydrochloride solution with hypromellose as an excipient (Irifrin® BK) demonstrated a decrease in severity of extra accommodation strain after 30 days of treatment. At the same time, Preparation B did not demonstrate its efficacy. In the experimental study, Irifrin® and Irifrin® BK were superior to Preparations A and B (without hypromellose as an excipient) as regards the peak mydriatic effect and the time required to reach maximal mydriasis. The peak phenylephrine concentrations in the aqueous humor within the eye anterior chamber were reached five minutes after instilling 1 drop of 2.5% phenylephrine with hypromellose solutions. These peaks were significantly higher than those observed after instilling Preparations A and B — phenylephrine in the same concentration but without hypromellose. Conclusion: the addition of hypromellose as an excipient to FDF of 2.5% phenylephrine solution helps to optimize pharmacodynamics and pharmacokinetics of the active ingredient by accelerating its inflow in the aqueous humor within the eye anterior chamber, increasing the topical bioavailability, and extending the exposure interval. It is likely that the above factors have underpinned the efficacy of Irifrin® and Irifrin® BK drugs used for the treatment of extra accommodation strain. The same results were obtained in this study comparing the clinical efficacy of 2.5% phenylephrine solution with hypromellose and its preparations without hypromellose used for the treatment of schoolchildren with extra accommodation strain amid myopia, as proven by the significant improvement of the accommodation indices during the treatment. Keywords: extra accommodation strain, mydriatic effect, peak concentration, rabbit, myopia, phenylephrine, hypromellose. For citation: Makhova M.V., Shikh E.V., Strakhov V.V. et al. Clinical and experimental rationale for using phenylephrine with hypromellose for the treatment of extra accommodation strain in patients with myopia. Russian Journal of Clinical Ophthalmology. 2023;23(1):33–38 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-33-38.